Nazi Hunger Politics: A History of Food in the Third Reich - Omar, Aziz (The International Journal of Sociology of Agriculture and Food, 2017)
A lot has been written about the German Third Reich’s incorporation of eugenics into their system of political administration. However, seldom has there been an exposé of the use of food by the Nazis in their racial cleansing operations. Gesine Gerhard’s seminal book Nazi Hunger Politics delves into the machinations of Hitler’s regime courtesy of Richard Walter Darré, the first Reich Minister of Food and Agriculture, and his protégé Herbert Backe who succeeded him in the same position. Across six chapters, the author insightfully links together the logistical and scientific aspects of food production and the feeding of the German masses with the Nazi ideological notions of unrestrained patriotism, racial superiority and purity, and eugenic pseudoscience.